The Impact of COVID-19 Curfew on Food Security Status, Eating Habits, and Health among Adults Living in Saudi Arabia: Food Security in Saudi Arabia during COVID-19 - Hanbazaza, Mahitab (Progress in Nutrition, 2021)
Objective: The COVID-19 pandemic and its related containment actions have impacted food security. This study aimed to assess food security status of adults in Saudi Arabia during, and describe their coping strategies, eating habits, and health during the COVID-19 curfew. Design: A cross-sectional study was conducted using an online survey, which included questions on sociodemographic characteristics, food security status, coping strategies, eating habits and self-rated health. Results: A total of 605 adults living in Saudi Arabia were recruited through an online survey. The overall prevalence of food insecurity was 28.4% (n= 172). Food insecurity was significantly higher among males with lower education and income level, and in participants living in rented properties. Numerous coping strategies were found to be significantly different between four types of food security groups. The total score of coping strategies was negatively associated with food security status (0.94±1.59, 2.78±2.44, 6.43±2.76, 7.34 ± 2.20, respectively, p < 0.001).  Food-insecure participants were significantly more likely to report poor/fair physical and mental health, compared to food-secure participants (p < 0.001). Food insecurity was significantly associated with changes in usual eating habits during the COVID-19 curfew (p < 0.001). Conclusion: The results showed that food insecurity can have a potential impact on adults’ health and eating habits. Governments need to take crucial actions and adopt comprehensive policies, both locally and globally, to ensure food security among populations.